In Silico Phylogeny of Magelang Taro (Colocasia esculenta) Using rbcL and matK DNA Barcodes - Kusumaningrum, Serafica Btari Christiyani; Kusumasri, Clara Ancilia Pramita; Ramadani, Shefa Dwijayanti (Jurnal Biologi Tropis, 2025)
Colocasia esculenta (taro) is an important tropical crop with high morphological diversity, particularly in Magelang Regency and City, Indonesia. However, morphologically based identification is often unreliable due to strong environmental influences, which limit its effectiveness in resolving genetic relationships among local varieties. Therefore, molecular approaches such as DNA barcoding are required to obtain more accurate and consistent genetic information. This study aimed to analyse the phylogenetic relationships among C. esculenta varieties from Magelang and to evaluate the effectiveness of the chloroplast genes rbcL and matK as DNA barcodes using an in silico approach. Secondary nucleotide sequence data for rbcL and matK were retrieved from the NCBI GenBank database and analysed using multiple sequence alignment with ClustalW in MEGA X. Phylogenetic trees were reconstructed using the Neighbour-Joining method with the Tamura-3-Parameter model and 1,000 bootstrap replications. At the same time, genetic distances were calculated using pairwise distance analysis. The results showed that matK exhibited a high level of sequence conservation, effectively resolving interspecific relationships within the genus Colocasia, but showed limited resolution at the intraspecific level. The rbcL gene displayed slightly higher nucleotide variation than matK, yet remained insufficient to discriminate local C. esculenta varieties clearly. Genetic distance analysis confirmed very low divergence among several varieties, indicating close evolutionary relationships. In conclusion, the use of rbcL or matK as single markers is inadequate for distinguishing local taro varieties. It is recommended that future studies employ multilocus approaches by combining rbcL–matK with faster-evolving markers, such as ITS, ITS2, or trnH–psbA, to achieve higher resolution at the intraspecific level and to support conservation and breeding programs of local taro germplasm.